Systematizing societal effects of transdisciplinary research. Issue 4 (27th September 2021) - Schäfer, Martina; Bergmann, Matthias; Theiler, Lena
Abstract: Over the past decade, transdisciplinary research has been faced with increasing demands by research policy and funding bodies to make its contribution to dealing with complex societal problems more transparent. In the literature, there is a range of methodological attempts to trace and describe the effects of transdisciplinary research, but these are characterized by inconsistent definitions regarding the scope and different forms of effects. This article aims to systematize the proposed categories and introduces a heuristic that can be used as a tool to sensitize researchers to intended effects ex ante and throughout the research process, as well as to reflect on the achieved effects ex post. The heuristic includes the temporal and spatial dimension of occurring effects (first-, second- and third-order) and characterizes possible forms of effects. It is validated and differentiated based on a multi-method empirical study involving 16 completed transdisciplinary research projects in different thematic areas. We propose a differentiation of frequently used categories, such as 'learning effects', and operationalize second- and third-order effects with the aim of ensuring a more consistent use of terminology in the transdisciplinary research community. We also specify methodical steps for a facilitated self-reflective application of the tool ex ante, supporting the research process, or ex post.